Aesthetic Transformation of Javanese Wayang Performances in the Digital Era - Sunardi, Sunardi; Saka, Putri Ananda; Sulastuti, Katarina Indah; Mulyana, Aton Rustandi; Ansari, Isa; Novianto, Wahyu; Kiswanto, Kiswanto; Putro , Renaldi Lestianto Utomo (Harmonia: Journal of Arts Research and Education, 2025)
This study examines how technological advancements have transformed the aesthetics of wayang performances in Java. Data collection methods include observations of wayang performances, interviews, literature reviews, and internet searches to capture the aesthetic transformation of wayang performances in the digital age. Given the existing literature’s tendency to discuss wayang performances within a limited scope, this research provides a more comprehensive contribution by positioning wayang performances as an integrated entity encompassing dalang creativity and audience response. Through the analysis of diverse wayang performances, the study demonstrates that aesthetic transformation is evidenced by the dalang’s hybrid presentation techniques, the emergence of novel story repertoires, and increased audience engagement. Significant findings from this study include the growth of dalang’s creative and adaptive capabilities, enhanced interpretative approaches in composing wayang stories, and the audience’s influence in shaping mass aesthetic trends. This study provides important contributions to the pedalangan (puppetry) and the relations of wayang, dalang, audience, and technology. Furthermore, this study contributes to the academic discourse on cultural adaptation in the digital age and provides pragmatic resources for the artistic development of Javanese puppetry.